The Profile of Gastrointestinal Stromal Tumors (GISTs) at Dr. M. Djamil General Hospital Padang, Indonesia: A Descriptive Study on 28 Patients - Aliska, Gestina; Novianti, Hera; Angraini, Desti; Liana, Nana; Nova, Riki; Rustam, Erlina (Frontiers on Healthcare Research, 2024)
Background: Gastrointestinal stromal tumors (GISTs) are the most frequently seen mesenchymal neoplasm in the digestive system. GISTs was originally described as smooth muscle tumor in the 1980s but advances in molecular diagnostic methods and immunohistochemistry moved GISTs into a different category from smooth muscle tumors. The study aims to report on epidemiological, clinical, immunochemical, and therapeutic characteristics of GISTs. Methods: We performed a retrospective descriptive study of 28 cases of GIST in the gastroenterology and general surgery departments of M. Djamil General Hospital Padang, Indonesia was conducted from January 2019 to December 2021. Data collection using medical records of patients in M. Djamil General Hospital Padang, Indonesia. We reported different data: Age, sex, symptoms, site, and immunohistochemistry of the tumor.  Results: Our study included 28 patients 18 males (64,3%) and 10 females (35.7%), with a median age range of 51-60 years. The presenting symptoms were abdominal mass (53.6%), abdominal pain (14.3%), bloody or dark-colored stools (14.3%), constipation (7.1%), fatigue (7.1%), and nausea and vomiting in 1 case (3.6%). Sixteen patients (57.1%) had a primary tumor and twelve patients (42.9%) had further metastatic lesions. The tumors were found in the stomach (21.4%), small intestine (14.3%), rectum (14.3%), and in other sites such as the retroperitoneal, liver, and distal pancreas. The immunohistochemical study was performed in seven cases (expression of  CD117 and DOG1), in four cases  CD117 was positive, while in three cases CD117 was negative. In two cases, the expression of DOG1 was positive, while in one case, it was negative. Eighteen patients with GIST (64.3%) underwent surgical procedures. A combination of surgical and chemotherapy was prescribed in 9 patients (32.1%). The chemotherapy regimen prescribed is imatinib. One patient is inoperable and has received symptomatic treatment. Conclusion : In conclusion, our result showed that GISTs are highest in the male population with an age range of 51-60 years. The most common symptom of GISTs is abdominal mass. Patients who have been diagnosed with GIST by histopathological examination do not always show positive expression in the immunohistochemical study. Surgical resection was indicated in the majority of patients, and a combination of surgery and chemotherapy is also prescribed as a treatment for patients with GIST.